Microbial Communities in Vermiculation Deposits from an Alpine Cave - Jurado, Valme; Gonzalez-Pimentel, Jose Luis; Miller, Ana Zelia; Hermosin, Bernardo; D’Angeli, Ilenia M.; Tognini, Paola; De Waele, Jo; Saiz-Jimenez, Cesareo (Frontiers in Earth Science, 2020)
Morgana Cave is located in Val di Scerscen, Central Italian Alps. The cave opens at an altitude of 2600 m a.s.l. close to the retreating glacier Vedretto di Scerscen, and its entrance was discovered 30 years ago hidden underneath the glacier. A characteristic of this cave is the occurrence of vermiculation deposits on the walls and ceiling. In general, the composition of the microbial communities from cave vermiculations is relatively unknown and rarely investigated. Here we present the data of a geomicrobiological study of vermiculations from an Alpine cave subjected to extreme climate conditions. The microbial communities were dominated by 13 main phyla of Bacteria, and contained negligible percentage (< 1%) of Archaea. The two major bacterial classes were Gammaproteobacteria and Betaproteobacteria, whose metabolic traits were mainly associated to the nitrogen cycle. In addition, psychrophilic and methanotrophic bacterial groups were identified. The occurrence of a large number of uncultured members at the lowest taxonomic ranks indicated the presence of still unexplored microbial taxa in the vermiculations.